Pleomorphic adenoma of the hard palate - Janardhan B Garde; Kanchan Raikwar; Adwait Kulkarni (Wolters Kluwer Medknow Publications, 2010)
Pleomorphic adenoma is the most common benign salivary gland tumor, which has elements of both epithelial and mesenchymal tissues. The tumor most commonly arises in the parotid or submandibular glands. Infrequently, it may arise from the minor salivary glands. We report a case of pleomorphic adenoma of minor salivary gland of palate in an 18-year-old young female patient for which the surgical treatment was rendered and with no evidence of recurrence.